Comparative interactions of withanolides and sterols with two members of sterol glycosyltransferases from Withania somnifera. Issue 1 (December 2015) - Pandey, Vibha; Dhar, Yogeshwar; Gupta, Parul; Bag, Sumit; Atri, Neelam; Asif, Mehar; Trivedi, Prabodh; Misra, Pratibha
Abstract Background Sterol glycosyltransferases (SGTs) are ubiquitous but one of the most diverse group of enzymes of glycosyltransferases family. Members of this family modulate physical and chemical properties of secondary plant products important for various physiological processes. The role of SGTs has been demonstrated in the biosynthesis of pharmaceutically important molecules of medicinal plants likeWithania somnifera . Results Analysis suggested conserved behaviour and high similarity in active sites ofWs SGTs with other plant GTs. Substrate specificity ofWs SGTs were analysed through docking performance ofWs SGTs with different substrates (sterols and withanolides). Best docking results ofWs SGTL1 in the form of stable enzyme-substrate complex having lowest binding energies were obtained with brassicasterol, transandrosteron andWs SGTL4 with solasodine, stigmasterol and 24-methylene cholesterol. Conclusion This study reveals topological characters and conserved nature of two SGTs fromW. somnifera (Ws SGTs) i.e.Ws SGTL1 andWs SGTL4. However, besides being ubiquitous in nature and with broad substrate specificity, difference betweenWs SGTL1 andWs SGTL4 is briefly described by difference in stability (binding energy) of enzyme-substrate complexes through comparative docking.